VACCINE FOR THE TREATMENT AND PREVENTION OF DRUG ADDICTION - V. S. Morozova; M. A. Myagkova; V. V. Suslov; S. A. Kedik (Разработка и регистрация лекарственных средств)
Medicines used for the treatment of drug addiction nowadays are ineffective. In the last decade, various schools around the world are developing a new approach: the therapeutic vaccine for the treatment of drug addiction. The vaccine injection raises the production of specific antibodies that bind to the drug when it is used and substantially reduces its concentration in the brain. The review describes the main approaches to the design of anti-drug vaccines, their composition, the problems faced by researchers in their development.